2018
DOI: 10.18203/2349-2902.isj20183723
|View full text |Cite
|
Sign up to set email alerts
|

Study of post-operative pulmonary complications in patients of emergency abdominal surgeries

Abstract: Background: Post-operative Pulmonary Complications (PPCs) form a significant chunk of post-operative morbidity. Their incidence varies from 2.7-23% in multiple studies. Pre-disposing factors can be divided as: pt. related: >60yrs, ASA class≥2 and COPD; procedure related: long surgeries (≥3hrs), emergency surgeries. Till now, most of the studies have focused on elective surgeries. In this study, I have studied morbidity and risk factors of PPCs in emergency abdominal surgeries.Methods: It is a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Kumar et al studied one hundred and fifty patients who underwent abdominal surgery, and of these, 16% developed PPCs and the highest incidence occurred in the emergency surgery group too [25]. Verma et al conducted a study of PPCs in patients of emergency abdominal surgeries and found that pre-operative abnormal chest X-ray changes were 3 times more common in the PPCs group as compared to the control group without PPCs [26]. In our study, no significant association was observed between this variable and the occurrence of PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al studied one hundred and fifty patients who underwent abdominal surgery, and of these, 16% developed PPCs and the highest incidence occurred in the emergency surgery group too [25]. Verma et al conducted a study of PPCs in patients of emergency abdominal surgeries and found that pre-operative abnormal chest X-ray changes were 3 times more common in the PPCs group as compared to the control group without PPCs [26]. In our study, no significant association was observed between this variable and the occurrence of PPCs.…”
Section: Discussionmentioning
confidence: 99%